2002
DOI: 10.4995/ia.2002.2619
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la garantía de suministro de agua a la agricultura. Una aplicación a la cuenca del Guadalquivir

Abstract: Los criterios de asignación de agua destinada al regadío influyen decisivamente en la vulnerabilidad a sequías hidrológicas en la Cuenca del Guadalquivir. El Plan Hidrológico de la Cuenca define específicamente los objetivos de garantía de suministro para usos agrarios. El grado de cumplimiento de estos objetivos es tributario de los criterios de reparto del agua disponible, y por tanto de la gestión de las reservas hidrológicas. El objetivo de este trabajo es evaluar la actual regla de asignación de dotacione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…On the basis of work by Go´mez-Ramos et al (2002), Pe´rez Blanco et al (2011) and Go´mez Go´mez and Pe´rez Blanco (2012), we adjust the PDF of the level of water stored in reservoirs at the beginning of the irrigation season using the Weibull function. This function assigns a probability (w) to each stored water level (s), measured as a percentage of the storage capacity, in La Campin˜a.…”
Section: Water Stock In Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of work by Go´mez-Ramos et al (2002), Pe´rez Blanco et al (2011) and Go´mez Go´mez and Pe´rez Blanco (2012), we adjust the PDF of the level of water stored in reservoirs at the beginning of the irrigation season using the Weibull function. This function assigns a probability (w) to each stored water level (s), measured as a percentage of the storage capacity, in La Campin˜a.…”
Section: Water Stock In Reservoirsmentioning
confidence: 99%
“…We found that the relevant variables explaining the percentage of TIR satisfied are water stored in reservoirs (measured as a percentage over total storage capacity) (s) and annual rainfall in mm (p). The relationship between the percentage of TIR satisfied (h(p,s)) and both of these variables are linear (Go´mez Ramos et al 2002). The parameters of the function are estimated using ordinary least squares (see Table 3).…”
Section: Traditional Decision Rulesmentioning
confidence: 99%
“…In these cases, the literature supports the use of Weibull functions for the adjustment of surface stored water PDFs. (Gómez-Ramos et al, 2002;Pérez et al, 2011;Gómez & Pérez, 2012). A Weibull function assigns a probability (w) to each amount of surface water stored (s), measured as a percentage over the dam storage capacity (DSC) of the SRB.…”
Section: Water Stored In Reservoirsmentioning
confidence: 99%
“…We found that the only relevant variable explaining the percentage of TIR satisfied in the past has been the runoff (r). The relationship between the percentage of TIR satisfied (h) and runoff (r) is linear (h ¼ h(r)) (Gómez-Ramos et al, 2002). The parameters of the function are estimated using ordinary least squares 7 .…”
Section: Second Stage: Decision Rulesmentioning
confidence: 99%
“…Aunque existen modelos estocásticos aplicados al análisis de las precipitaciones (Martin et al, 2001) y del agua embalsada (Gómez Ramos et al, 2002), hasta el momento, estos no han sido integrados en un único modelo de evaluación del riesgo y de las consecuencias de la insuficiencia de agua para la agricultura de regadío. El modelo presentado en este artículo supone un avance en ese sentido y permite calcular el impacto de la escasez de agua (medido en porcentaje de la evapotranspiración satisfecha por precipitaciones y por regulación hídrica) sobre la producción física (medida en kilogramos por hectárea).…”
Section: Introductionunclassified